2016
DOI: 10.1371/journal.pone.0161375
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Caffeine Supplementation on Physiological Responses to Submaximal Exercise in Endurance-Trained Men

Abstract: ObjectivesThe aim of this study was to evaluate the effects of caffeine on physiological responses to submaximal exercise, with a focus on blood lactate concentration ([BLa]).MethodsUsing a randomised, single-blind, crossover design; 16 endurance-trained, male cyclists (age: 38 ± 8 years; height: 1.80 ± 0.05 m; body mass: 76.6 ± 7.8 kg; : 4.3 ± 0.6 L∙min-1) completed four trials on an electromagnetically-braked cycle ergometer. Each trial consisted of a six-stage incremental test (3 minute stages) followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
30
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 48 publications
5
30
2
2
Order By: Relevance
“…Nevertheless, the mechanisms responsible, and the short-and long-term associated health risks are, at present, unclear (De Giuseppe et al 2019). Similarly, the effects of caffeine on heart rate agree with those previously reported (Fredholm et al 1999;Glaister et al 2016), in that caffeine typically reduces resting heart rate by ~ 3 b•min -1 , with the effect dissipating as exercise intensity increases (Glaister et al 2016). Moreover, caffeine typically increases heart rate during time-trials due to the corresponding caffeine-induced increase in time-trial intensity (Glaister and Moir 2019).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Nevertheless, the mechanisms responsible, and the short-and long-term associated health risks are, at present, unclear (De Giuseppe et al 2019). Similarly, the effects of caffeine on heart rate agree with those previously reported (Fredholm et al 1999;Glaister et al 2016), in that caffeine typically reduces resting heart rate by ~ 3 b•min -1 , with the effect dissipating as exercise intensity increases (Glaister et al 2016). Moreover, caffeine typically increases heart rate during time-trials due to the corresponding caffeine-induced increase in time-trial intensity (Glaister and Moir 2019).…”
Section: Discussionsupporting
confidence: 82%
“…Although most of the physiological responses to caffeine measured in the present study were the same as reported previously, there were some anomalous findings. The effect of caffeine on RER is particularly confusing in that while the increase at rest fits with previous reports (Glaister et al 2016), the submaximal and time-trial responses do not. In a recent meta-analysis, Glaister and Gissane (2018) found no effect of caffeine on RER during submaximal exercise at 60 -85% V O 2max; indeed, the tendency was for RER to be reduced with caffeine, though there was considerable between-study heterogeneity.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…effect between caffeine and exercise intensity on RER, with values reducing, relative to placebo, as exercise intensity increases. 48,73 Although the mechanisms to explain that response are unclear, 6 it is possible that the absence of an effect of caffeine on RER during the time trials is due to caffeine counteracting the increase in RER that would be expected after an increase in exercise intensity.…”
mentioning
confidence: 99%